Geology and tectonics of the Central Crystallines of northeastern Kumaun Himalaya, India - Paul, S. K. (Journal of Nepal Geological Society, 1998)
Four major geo-tectonic domains are encountered in the northeastern Kurnaun Himalaya between the Ramganga and Kali rivers. These tectonic domains are: (1) Sedimentary Terrain of the south, (2) Lower Central Crystallines, (3) Upper Central Crystallines, and (4) Tethyan Supergroup in the north. The Sedimentary Terrain comprises of the Berinag, Damtha and Tejam groups. The Lower Central Crystallinel are divided into Rungling and Munsiari formations, separated by a thin lensoidal wedge of sedimentary sequence of the Sirdang Sedimentary Zone, which is the continuation of the Nawakot Complex in western Nepal. The rocks of the Nawakot Complex wrap around the Chhiplakot Crystallines of the Munsiari Formation in Nepal and join with the Berinag Formation in northeastern Kumaun region. The Munsiari Formation has been divided into Phalyati, Baram, Chhiplakot and Khet members.The Upper Central Crystallines are represented by the rocks of the Vaikrita Group, and form the basement for the Tethyan sedimentary sequence. The Vaikrita Group is divided into four formations namely Joshimath, Pandukeshwar, Pindari and Martoli. The Joshimath Formation is further subdivided into Dar and Sela members whereas the Martoli Formation is subdivided into Budhi Schist and Dugtu members. The southern contact of the Munsiari Formation with the Lesser Himalayan sedimentary sequence forms a tectonic boundary designated as the Munsiari Thrust or MCT I. The southern contact of the Rungling Formation with the rocks of the Sirdang Sedimentary Zone forms another tectonic boundary designated as the Rungling Thrust or MCT II. The Munsiari Thrust (MCT I) has been interpreted to terminate near Chainpur in western Nepal at its branch point. The contact between the Upper Central Crystallines and the Lower Central Crystallines is designated as the Vaikrita Thrust or Main Central Thrust (MCT). The quartzite of the Berinag Formation exposed in the Sirdang Sedimentary Zone thrust over the Munsiari Formation along the Pangla Thrust. The northern part of the Martoli Formation of the Vaikrita Group is characterised by concordant relationship with the Ralam Conglomerate and also the Garbayang Formation of the Tethyan Super Group. Either side of this contact zone is characterised by a series of minor southward thrusts and associated shear planes, which are subsequently cut by a series of normal faults and related shear planes exhibiting down to the NE oblique slip displacement. The shear zone containing contractional and superposed extensional structures at the northern portion of the Vaikrita Group and at the basal part of the Tethyan Supergroup is designated as Tethyan Shear Zone.